Estudo da associação entre polimorfismos na G6PD e infecções fúngicas em portadores de Leucemia Mielóide Aguda acompanhados no Hemocentro do Amazonas - Freitas, Noeme Henriques (2020)
Patients with acute myeloid leukemia (AML) show at higher risk for several infections, including fungal infections, which is one of the main causes of morbidity and mortality. Glucose-6-phosphate dehydrogenase (G6PD is an enzyme located in all cells, with primordial function to protect against oxidative stress in erythrocytes, however, very necessary in leukocytes for the production of its basic and acid proteases used to destruction of invading microorganisms. Objective: To evaluate whether polymorphisms in the G6PD gene concomitantly with fungal infections (IF) are associated with clinical and morbidity in patients diagnosed with AML followed up at the blood foundationfrom Amazon(FHEMOAM). Methodology: We performedan active search for patients and review of medical records. G6PD mutations was determination of was performed using the qPCR technique and subsequent genetic sequencing to confirm the mutations. Results: A total of 157 patients were involved in the study, being 91 (58%) men and 66 (42%) women. The most prevalent AML subtype in the studied group was M3 in 63 patients (40.12%), followed by M5 in 33 patients (21.02%), M2 in 21 patients (13.37%) and M4 in 15 patients (9.55%), with similar prevalence between genders. The prevalence of fungal infections was identical between genders, however, bruising (P = 0.004), vomiting (p = 0.016) and cardiac changes (P <0.001) was higher in females, while persistent cough (p = 0.049) and Diarrhea (p <0.001) in males. Eighteen patients were diagnosed with two G6PD mutations, with 08 (5.1%) for c.202G/A, 18 (11.5%) for c.376A/G and 04 (2.5%) for both mutations concomitantly (c. 202G/A / c.376A/G). Although the carriers of the mutations were more frequently affected with fungal infections, 9.8% in carriers for c202G/A vs 3.4% in normal, 12.2% for c376G/A vs 11.2% in normal and 7, 3% for both c202G/A / c.376A/G vs 0.7%, this incidence was not significant, although we believe that with a larger sample number of carriers of mutations and fungal infections, this data would be significant. Otherwise, the prevalence of death in patients with the mutations found was much higher when affected by FI (P <0.001). We believe that the determination of G6PD polymorphisms will allow the development of monitoring strategies, early diagnosis and appropriate and targeted treatment for AML, as well as evaluating its activity may help to identify AML patients at higher risk for FI, allowing the design of more therapeutic and surveillance strategies intensive